2019
DOI: 10.1002/adem.201900821
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Initial Defects on Impact Ignition of Aluminum/Polytetrafluoroethylene Reactive Material

Abstract: Aluminum/polytetrafluoroethylene (Al/PTFE) reactive material is a typical multifunctional energetic material, which can release enormous energy under impact loading. To clarify its ignition mechanism, a Split Hopkinson pressure bar (SHPB) is used to conduct the impact ignition experiment on reactive materials with different initial defects. The experimental results show that the measured minimum specific incident energy that can cause the ignition for the specimen without pre‐impact (MSed specimen) increases s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Under uniaxial impact loading, microcracks are generated and expand due to the deformation of the holes, resulting in the reduction of compressive strength. [ 17,26 ] The confining pressure exposes the specimen to triaxial compressive stress loading, preventing microporosity deformation and increasing the specimen's compressive strength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under uniaxial impact loading, microcracks are generated and expand due to the deformation of the holes, resulting in the reduction of compressive strength. [ 17,26 ] The confining pressure exposes the specimen to triaxial compressive stress loading, preventing microporosity deformation and increasing the specimen's compressive strength.…”
Section: Resultsmentioning
confidence: 99%
“…The decomposition products come into contact with the metal particles and undergo a chemical reaction. For the studied Al/PTFE reactive material, the research [ 17 ] has indicated that the reaction threshold has a damage sensitization phenomenon. Specimens containing initial damage were obtained using preimpact experiments, and their reactive thresholds were compared with those of normal specimens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation